Violência escolar na escola Basílio de Carvalho - SILVA, Rosivani Costa da (2024)
This monographic work has as its main focus information on violence with faculty in the State School of elementary and secondary education Basílio de Carvalho. People who contributed to the realization of this research were altogether: two teachers, the Director of the institution, four high school students, two males and two females. Starting from this perspective, the work had as objective 1) understand how arose along the educational history, the issue of violence in the school space be it physical, verbal or other character, 2) what are the expectations and challenges that it professionals are on your desktop. .3) which reflects the violence in life and in relations of students. Soon, the school has knowledge of what occurs daily in this respected educational institution. As a result of all these required procedures, will be well evidenced more conflicts.